Multi-organ FGF21-FGFR1 signaling in metabolic health and disease - Kaur, Namrita; Gare, Sanskruti Ravindra; Shen, Jiahan; Raja, Rida; Fonseka, Oveena; Liu, Wei (Frontiers in Cardiovascular Medicine, 2022)
Metabolic syndrome is a chronic systemic disease that is particularly manifested by obesity, diabetes, and hypertension, affecting multiple organs. The increasing prevalence of metabolic syndrome poses a threat to public health due to its complications, such as liver dysfunction and cardiovascular disease. Impaired adipose tissue plasticity is another factor contributing to metabolic syndrome. Emerging evidence demonstrates that fibroblast growth factors (FGFs) are critical players in organ crosstalk via binding to specific FGF receptors (FGFRs) and their co-receptors. FGFRs activation modulates intracellular responses in various cell types under metabolic stress. FGF21, in particular is considered as the key regulator for mediating systemic metabolic effects by binding to receptors FGFR1, FGFR3, and FGFR4. The complex of FGFR1 and beta Klotho (β-KL) facilitates endocrine and paracrine communication networks that physiologically regulate global metabolism. This review will discuss FGF21-mediated FGFR1/β-KL signaling pathways in the liver, adipose, and cardiovascular systems, as well as how this signaling is involved in the interplay of these organs during the metabolic syndrome. Furthermore, the clinical implications and therapeutic strategies for preventing metabolic syndrome and its complications by targeting FGFR1/β-KL are also discussed.